Use of High-Dose Chemotherapy in Front-Line Therapy of Infants Aged Less Than 12 Months Treated for Aggressive Brain Tumors - Guidi, Milena; Giunti, Laura; Buccoliero, Anna Maria; Santi, Mariarita; Spacca, Barbara; De Masi, Salvatore; Genitori, Lorenzo; Sardi, Iacopo (Frontiers in Pediatrics, 2020)
Introduction: Malignant brain tumors in infants less than 12 months of age are extremely rare, and they have poor prognosis. We evaluated genetic characteristics and response rates of infants with congenital brain tumors subjected to high-dose chemotherapy and autologous stem cell transplant after gross total tumor resection. Materials and Methods: In total, 10 infants, aged less than 12 months, were enrolled in this study. The median age was 56 days (range: 1–279 days). Pathological examination demonstrated the following: four anaplastic astrocytomas, two glioblastomas, two central nervous system (CNS) embryonal tumors, not otherwise specified (NOS), and two atypical teratoid/rhabdoid tumors. Results: All patients were exposed to induction chemotherapy regimen, two high-dose chemotherapy courses, and autologous stem cell transplant after maximal surgery. At 1–3–5 years, the global overall survival (OS) was 90, 70, and 70% and the progression-free survival (PFS) was 80–60 and 60%. In all the patients, the copy number variants (CNVs) profile was analyzed using the SNP/CGH array approach. To investigate the clinical relevance of germline SMARCB1 mutation in AT/RT patients, we performed sequence analysis of the coding regions. The two patients with AT/RT were found to have germline SMARCB1 mutations. No BRAF mutations were found, and only NTRK gene fusion was present in one patient. We also have examined the association with OS and PFS and different histological subtypes of infant CNS proving that high-grade astrocytoma has better overall survival than other tumor types (p: 0.007 and p: 0.0590). Conclusion: High-dose chemotherapy regimen represents a valid therapeutic approach for congenital brain tumors with a high rate of response. The molecular analysis has to be analyzed in all infants' brain tumor types. High-grade gliomas are characterized by a better prognosis than other histologies of infant CNS.